Preemptive Living-Related Kidney Transplantation Is a Cost-Saving Strategy Compared With Post-dialysis Kidney Transplantation in Thailand - Phongphithakchai, Atthaphong; Phisalprapa, Pochamana; Kositamongkol, Chayanis; Premasathian, Nalinee; Larpparisuth, Nuttasith; Skulratanasak, Peenida; Vongwiwatana, Attapong (Frontiers in Medicine, 2022)
Background Compared with other kidney replacement therapies, preemptive kidney transplantation (KT) provides better clinical outcomes, reduces mortality, and improves the quality of life of patients with end-stage kidney disease (ESKD). However, evidence related to the cost-effectiveness of preemptive living-related KT (LRKT) is limited, especially in low- and middle-income countries, such as Thailand. This study compared the cost-effectiveness of LRKT with those of non-preemptive KT strategies. Methods Cost and clinical data were obtained from adult patients who underwent KT at Siriraj Hospital, Mahidol University, Thailand. A decision tree and Markov model were used to evaluate and compare the lifetime costs and health-related outcomes of LRKT with those of 2 KT strategies: non-preemptive LRKT and non-preemptive deceased donor KT (DDKT). The model’s input parameters were sourced from the hospital’s database and a systematic review. The primary outcome was incremental cost-effectiveness ratios (ICERs). Costs are reported in 2020 United States dollars (USD). One-way and probabilistic sensitivity analyses were performed. Results Of 140 enrolled KT patients, 40 were preemptive LRKT recipients, 50 were non-preemptive LRKT recipients, and the rest were DDKT recipients. There were no significant differences in the baseline demographic data, complications, or rejection rates of the three groups of patients. The average costs per life year gained were $10,647 (preemptive LRKT), $11,708 (non-preemptive LRKT), and $11,486 (DDKT). The QALY gained of the preemptive option was 0.47 compared with the non-preemptive strategies. Preemptive LRKT was the best-buy strategy. The sensitivity analyses indicated that the model was robust. Within all varied ranges of parameters, preemptive LRKT remained cost-saving. The probability of preemptive LRKT being cost-saving was 79.4%. Compared with non-preemptive DDKT, non-preemptive LRKT was not cost-effective at the current Thai willingness-to-pay threshold of $5113/QALY gained. Conclusions Preemptive LRKT is a cost-saving strategy compared with non-preemptive KT strategies. Our findings should be considered during evidence-based policy development to promote preemptive LRKT among adults with ESKD in Thailand.